Controlled spreading of melted fillers and precision micro-brazing based on a micro-scale binary cooperative complementary interface design strategy. Issue 15 (1st August 2021) - Chen, Haiyan; Zhao, Shuai; Nai, Xin; Miao, Lele; Shen, Zhikang; Liu, Xiaochao; Cao, Jian
Abstract: For improving the brazing joint precision of ceramics and metals, a micro-scale binary cooperative complementary interface was used to achieve precise control of the wetting and spreading of melted fillers. By analytical calculation and numerical simulation, the study revealed the influence of structural parameters of the binary cooperative complementary interface on the wetting behavior of fillers, which was verified by the wetting experiment. The experimental results showed that the Ag–28Cu filler was difficult to wet on smooth ceramic substrates. For ceramic with the binary cooperative complementary microstructure, the inhibitory effect of the ceramic phase zone on the wetting and spreading of fillers was dominant when the width of copper phase zone is small. With increasing the width of cooper phase zone, the copper phase zone gradually played a leading role in the wetting and spreading of fillers. A good wetting and spreading of fillers in the joint area and precise control of the fillers boundary were achieved by the micro-scale binary cooperative complementary interface.